Effect of Predialysis Recombinant Human Erythropoietin on Early Survival After Hemodialysis Initiation in Patients With Chronic Kidney Disease: Co‐JET Study. Issue 6 (7th December 2016) - Watanabe, Yuzo; Akizawa, Tadao; Saito, Akira; Gejyo, Fumitake; Suzuki, Masashi; Nishizawa, Yoshiki; Tomino, Yasuhiko; Tsubakihara, Yoshiharu; Akiba, Takashi; Hirakata, Hideki; Kawanishi, Hideki; Bessho, Masami; et al.
Abstract: Progression of anemia in patients with chronic kidney disease (CKD) is associated with an increased risk of death and hospitalization. It is not sufficiently clear whether treating renal anemia with recombinant human erythropoietin (rHuEPO) has a beneficial effect on early survival after hemodialysis (HD) initiation in patients with CKD. The study was an open‐label multicenter retrospective cohort study to evaluate the relationship between rHuEPO treatment and early survival after HD initiation in patients with CKD. Predialysis patients with CKD were divided into two groups: an rHuEPO‐treated group (rHuEPO group) and a non‐treatment group. The primary endpoint was all‐cause mortality in the year after HD initiation. A total of 3261 patients were enrolled (2275 in the rHuEPO group and 986 in the non‐treatment group). One‐year survival was 95.36% in the rHuEPO group and 90.36% in the non‐treatment group. The survival rate was significantly higher in the rHuEPO group ( P < 0.0001). The results of multivariate analysis confirmed that predialysis treatment with rHuEPO is a predictor for reduced mortality risk (hazard ratio = 0.61, 95% confidence interval: 0.42–0.87, P = 0.006). Risk for the composite event of death/hospitalization was also lower in the rHuEPO group (hazard ratio = 0.88, 95% confidence interval: 0.78–0.98, P = 0.026). The results of this study suggest that treatment with rHuEPO can decrease early mortality risk after initiation of HD in patients with CKD. A prospective study is needed to further investigate early survival after HD initiation.